Asphalt Chemistry (Global Journal of Science Frontier Research, 2015)
The students were taught to generate oil (binder) from recycled asphalt pavement (aggregate) using a Buchi Rotavapor R-15 for submission for elemental analysis (C, N, H, O) and engineering rheology testing and microbial growth. We obtained 18 samples from Oklahoma Department of Transportation divisions and two construction companies to compare the physical and chemical properties of these samples.
Keywords: comparison of various samples of recycled asphalt pavement